Pengaruh Latihan Hurdle Drill Terhadap Kecepatan Tendangan Sabit Pesilat Padepokan Pagar Nusa Hizzbi - Ahmad Bashori; Yuskhil Mushofi; Winarno; Ary Artanty; Ahmad Junaidi; Paulus Rah Adi Pawitra (Universitas Singaperbangsa Karawang, 2024)
The martial art of pencak silat is an original cultural heritage of the Indonesian people that has received international recognition. Pencak silat itself has one of the best techniques, namely the sickle kick technique. The sickle kick itself must be practiced properly so that it can give maximum results to a fighter. The purpose of this study was to determine the effect of hurdle drill training on the speed of the sickle kick of the Hizzbi fencing fighter. The method used is quantitative with pre-experimental designs with the type of one-group pretest-posttest design using only one group. While the population, namely the fighters of the Pagar Nusa Hizzbi group, amounted to 17 fighters with the sample technique used, namely saturated sampling. The data analysis technique used the t-test while the research time was for 6 weeks with a training frequency of 3 times each week by applying Hurdle Drill training. Based on the results of research and data analysis after hypothesis testing, the t-count result is 2.77 while the t-table result is 2.113. Therefore, in the value of tcount> ttable 2.77> 2.113 so that it can be concluded that there is an influence on hurdle drill training on the results of the sickle kick speed of fighter fencing fencing nusa Hizzbi this research hypothesis is accepted.